Methodological aspect of assessing students’ achievements using a test check (Pedagogy of Higher and Secondary Education, 2014)
Ivanchenko V. O. Methodological aspect of assessing students’ achievements using a test check.This article describes the principle methodological aspects of estimating higher school students’ knowledge using a test check. The author reveals the main items of the process of measuring the quality of knowledge through a test check.
Keywords: methodological aspects; assessment; test check; measurement process